Enchancing Students’ Mathematical Problem Solving Ability and Self-Regulated Learning by Using Realistic Mathematics Education - Rintari, Rintari; Sumarmo, Utari; Kustiana, Asep ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This article reported the findings of an experiment research having a goal to enchance students’ mathematical probelm solving ability (MPSA) and self regulated learning (SRL) by using realistic mathematics education (RME). Subjects of this  research were 60 seventh grade students of a Yunior High School in Garut, and the instruments this research were an essay MCTA test,  and a SRL scale. The research found that the grades of MPSA of students getting treatment with RME were higher than the grades of students taught by scienctific approach, however those grades were at low grades qualification. In addition, there were no different grades on student’s SRL.  Beside that, stdudents in both classess still encountered difficulties on solving MPSA tasks, and there was no association between student’s MCTA and student’s SRL.Keyword: mathematical problem solving ability, mathematical self regulated learning, realistic mathematics education,